The Effects of Macroeconomic Variables on the Determination of Bank Credit Rate of Usury-Free-Banking in Iran - Fallah, Shahrbanou; Shahinpour, Ali; Sattary, Ali (International Journal of Economics and Financial Issues, 2018)
The study has used Auto Regressive Distributed Lag method to estimate the effects of independent variables on the dependent variable. According to findings, the impact inflation rate on bank credit rate is positive in short – run, so that the impact of this variable has been effective on bank credit rate after one year delay on dependent variable. The reel per capita gross domestic product alters the banking credit rates toward the positive direction. The short – run impact of legal reserve rate on bank credit rates is positive. The effects of inflation rate, GDP, and legal reserve rate variables are positive on the bank credit rate. Thus, the Fisher hypothesis is confirmed in Iranian context. Error correction coefficient links the speed of the short-run variable fluctuations to the long-run equilibrium amount i.e. the short-run imbalances of dependent variable decreases 19% annually and moves to the long-run equilibrium. Keywords: Macroeconomic Variables, Bank Credit Rate, Usury- Free- Banking JEL Classifications: E51, E58, E52